Countering violent extremism and terrorism: assessing domestic and international strategies - Von Hlatky, Stéfanie (Human dimensions in foreign policy, military studies, and security studies, 2019)
"Since 9/11, counterterrorism has become a national and international priority. Research on violent extremism and terrorism, from homegrown threats to foreign fighters, has adapted accordingly but has not always translated into policymaking. Extremism can be traced to no single cause, and yet governments and law-enforcement agencies continue to spend millions on prevention efforts. Contributors to this book identify persistent challenges for counterterrorism and countering violent extremism and provide analysis from a variety of academic and professional perspectives. Countering Violent Extremism and Terrorism cautions against adopting a causal model to understand violent extremism and takes a critical look at how states have managed to cope with the global phenomenon of terrorism. By drawing on the expertise of researchers and practitioners from government, law enforcement, and the military, contributors identify past failures and offer guidance on how to correct these mistakes. With the collective goal of developing more effective strategies, the authors dispel common myths, discard counterproductive tactics, and point to countries in which policies have functioned as intended. As some terrorist organizations’ influence wanes, others innovate and thrive, further challenging a state apparatus that is slow to adapt to these mutating threats. An essential and timely book, Countering Violent Extremism and Terrorism seeks to change how governments and policymakers consider and respond to security threats."